The contribution of honey bees, flies and wasps to avocado (Persea americana) pollination in southern Mexico - Perez-Balam, Jesica; Quezada-Euan, Jose Javier; Alfaro-Bates, Rita; Medina, Salvador; McKendrick, Lorraine; Soro, Antonella; Paxton, Robert J (Journal of Pollination Ecology, 2012)
Although avocado is native to Mexico, there are no comparative measures in this country on the performance of its flower visitors as pollinators. The contribution of honey bees, flies and wasps to the pollination of avocado from tropical Mexico was assessed by comparing abundance, speed of flower visitation, quantity of pollen carried per individual and pollen deposited on virgin flowers after single visits. The values of abundance and frequency of flower visitation with pollen deposition were combined to obtain a measure of pollinator performance (PP). The most abundant insects on avocado were flies (mean ± SE: 15. 2 ± 6.2), followed by honey bees (9.4 ± 6.3) and wasps (4.2 ± 3.1) (ANOVA F = 91.71, d.f. = 2,78; P < 0.001). Honey bees and wasps visited similar number of flowers (8.2 ± 3.1 and 7.5 ± 2.6 respectively), and more than flies (4.1 ± 1.2) in the same time period (F = 17.63; d.f. = 2,33; P < 0.01). Although flies carried far more avocado pollen on their bodies (44.9 ± 16.8 grains) compared with honey bees and wasps, (21.3 ± 6.2 and 23.8 ± 8.11 grains, respectively; H = 26.522, df = 2, P = 0.001), the number of pollen grains deposited on a stigma after a single visit was similar for the three taxa (2-5). There was evidence for a significant and similarly positive PP of both honey bees and flies as avocado pollinators over wasps, given their abundance, potential for pollen transport and deposition of pollen on stigmas.